Interlaboratory Study of Immunochromatography for the Rapid Determination of Cadmium Concentrations in Cereals and Soybeans. (27th November 2019) - Abe, Kaoru; Nakamura, Katsuo; Naito, Shigehiro
Abstract: Cadmium (Cd) is one of the most toxic heavy metals to humans. To prevent the distribution of Cd-contaminated food, a simple and quick on-site test for measuring Cd concentrations in agricultural products is needed. Recently, an immunochromatography kit developed for determining Cd in rice was reported to be useful for determining Cd in many other crops. We conducted an interlaboratory study to evaluate the kit for determining Cd in cereals (wheat and rice) and soybeans. Ten test materials were used, and 12 test samples including two sets of blind duplicates were distributed to 12 laboratories in Japan. The Cd recoveries (relative to certified values or values determined by inductively coupled plasma-MS) from all test materials were 84.6–125.1%. Repeatability RSD values of the test materials ranged from 8.8 to 14.8%. Reproducibility RSD values ranged from 13.4 to 27.6%, averaging 21.3%. The Horwitz ratio ranged from 0.61 to 1.36. The reproducibility was within the range of ELISA results for measuring toxins and allergens in food. Our results indicated that the kit was an inexpensive, reliable tool for quick and easy on-site determination of Cd in cereals and soybeans.